Approval of work / Muhammad Ariff Imran Ruzlan - Muhammad Ariff Imran, Ruzlan (2017)
The report contains statements about the method of construction work. Basis for Management Development Air Pahang Berhad for the new office. Topics represented in this report is very important for job approval. The method in this report for the purpose of making it the supervisor reports to understand the progress of work flow method which starts up the finishing work. In addition, there are figures, drawings, attachments that are collected from the company are included in the report. This content contains information for the project and have the information that will be tasked to ensure the success of the project. It also has a scope of work that has been assigned to implement the project. There is some information on the approval form work and also the procedure for implementation of construction works on site. Any reference to the implementation of the work will be referred by government departments like Majlis Daerah Bera, Jabatan Kerja Raya (JKR), Tenaga Nasional Berhad (TNB), Jabatan Bomba & Penyelamat Malaysia (Fire & Rescue Department of Malaysia) For the implementation of the work will have some requirement such as Quality Planning (QP), Quality Assurance (QA) and Quality Control (QC) so that the procedure can be carried out properly. There is a method statement for checked and tested by the Enforcement Officer to validate these methods. The process also works in the body to facilitate the work on site. Some descriptions have been made to describe the work of the observation during practical training. Some of the problems and possible solutions have been created to facilitate the work on the next site.